Geología de los cuadrángulos de Paita, Piura, Talara, Sullana, Lobitos, Quebrada. Seca, Zorritos, Tumbes, Zarumilla. Hojas: 11-a, 11-b, 10-a, 10-b, 9-a, 9-b, 8-b, 8-c, y 7-c – [Boletín A 54] - Palacios Moncayo, Oscar (1994)
190 p.